Longitudinal hemodynamics in acute phase of treatment with labetalol in hypertensive pregnant women to predict need for vasodilatory therapy. (1st December 2016) - Stott, D.; Bolten, M.; Paraschiv, D.; Papastefanou, I.; Chambers, J. B.; Kametas, N. A.
Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from the abstract to view the translations. This article has been selected for Journal Club. Click here to view slides and discussion points. ABSTRACT: Objective: Hypertensive pregnant women who do not respond to treatment with labetalol to control blood pressure (BP), but require vasodilatory therapy, progress rapidly to severe hypertension. This could be delayed by early recognition and individualized treatment. In this study, we sought to create prediction models from data at presentation and at 1 h and 24 h after commencement of treatment to identify patients who will not have a sustained response to labetalol and therefore need vasodilatory therapy. Methods: The study population comprised 134 women presenting with hypertension at a UK hospital. Treatment with oral labetalol was administered when BP was > 150/100 mmHg or > 140/90 mmHg with systemic disease. BP and hemodynamic parameters were recorded at presentation and at 1 h and 24 h after commencement of treatment. Labetalol doses were titrated to maintain BP around 135/85 mmHg. Women with unresponsive BP, despite labetalol dose maximization (2400 mg/day), received additional vasodilatory therapy with nifedipine. Binary logistic and longitudinal (mixed‐model) data analyses were performed to create prediction models anticipating the likelihood of hypertensive women needing vasodilatory therapy. The prediction models were created from data at presentation and at 1 h and 24 h after treatment, to assess the value of central hemodynamics relative to the predictive power of BP, heart rate and demographic variables at these intervals. Results: Twenty‐two percent of our cohort required additional vasodilatory therapy antenatally. These women had higher rates of severe hypertension and delivered smaller babies at earlier gestational ages. The unresponsive women were more likely to be of black ethnicity, had higher BP and peripheral vascular resistance (PVR), and lower heart rate and cardiac output (CO) at presentation. Those who needed vasodilatory therapy showed an initial decrease in BP and PVR, which rebounded at 24 h, whereas BP and PVR in those who responded to labetalol showed a sustained decrease at 1 h and 24 h. Stroke volume and CO did not decrease during the acute phase of treatment in either group. The best model for prediction of the need for vasodilators was provided at 24 h by combining ethnicity and longitudinal BP and heart rate changes. The model achieved a detection rate of 100% for a false‐positive rate of 20% and an area under the receiver–operating characteristics curve of 0.97. Conclusion: Maternal demographics and hemodynamic changes in the acute phase of labetalol monotherapy provide a powerful tool to identify hypertensive pregnant patients who are unlikely to have their BP controlled by this therapy and will consequently need additional vasodilatory therapy. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd. RESUMEN Objetivo: Las embarazadas hipertensas que no responden al tratamiento con labetalol para el control de la presión arterial (PA), pero que requieren terapia vasodilatadora, evolucionan rápidamente hacia una hipertensión severa. Ésta se puede retrasar mediante un diagnóstico precoz y un tratamiento individual. En este estudio se ha tratado de crear modelos de predicción a partir de datos al inicio del tratamiento y al cabo de 1 hora y de 24 horas después del mismo, para identificar a las pacientes que no mostrarán una respuesta constante al labetalol y que por lo tanto necesitarán terapia vasodilatadora. Métodos: La población de estudio incluyó 134 mujeres con hipertensión en un hospital del Reino Unido. El tratamiento con labetalol por vía oral se administró cuando la PA fue >150/100 mm de Hg o >140/90 mm de Hg con enfermedad multisistémica. Se registró la PA y los parámetros hemodinámicos tanto al inicio como al cabo de 1 h y de 24 h después del inicio del tratamiento. Las dosis de Labetalol se ajustaron para mantener la PA en torno a los 135/85 mm de Hg. Las mujeres cuya PA no produjo respuesta, a pesar de haberles administrado la dosis máxima de labetalol (2400 mg/día), recibieron terapia vasodilatadora adicional con nifedipino. Se realizaron análisis de datos mediante logística binaria y longitudinal (modelo mixto), para crear modelos de predicción con los que pronosticar la probabilidad de la necesidad de terapia vasodilatadora en mujeres hipertensas. Los modelos de predicción se crearon a partir de datos al inicio y al cabo de 1 hora y 24 horas del tratamiento, para evaluar el valor de los parámetros hemodinámicos principales con respecto a la capacidad predictiva de la PA, la frecuencia cardíaca y las variables demográficas en estos intervalos. Resultados: El 22 % de la cohorte necesitó terapia vasodilatadora adicional antes del parto. Estas mujeres tuvieron tasas más altas de hipertensión grave y neonatos más pequeños en edades gestacionales más tempranas. Las mujeres que no respondieron al tratamiento fueron con más frecuencia de raza negra, tuvieron la PA y la resistencia vascular periférica (RVP) más alta, y la frecuencia cardíaca y el gasto cardíaco (GC) más bajos al inicio del tratamiento. Aquellas que necesitaron terapia vasodilatadora mostraron un descenso inicial de la PA y la RVP, que se recuperó al cabo de 24 h, mientras que la PA y la RVP en las que respondieron al labetalol mostraron una disminución constante al cabo de 1 h y de 24 h. El volumen sistólico y el GC no disminuyeron durante la fase aguda del tratamiento en ninguno de los grupos. El mejor modelo para la predicción de la necesidad de vasodilatadores se obtuvo a las 24 h mediante la combinación de la etnia con los cambios longitudinales de la PA y la frecuencia cardíaca. El modelo alcanzó una tasa de detección del 100% para una tasa de falsos positivos del 20% y un área bajo la curva de características operativas del receptor de 0, 97. Conclusión: Los datos demográficos maternos y los cambios hemodinámicos en la fase aguda de la monoterapia con labetalol constituyen una herramienta poderosa para identificar a las pacientes embarazadas hipertensas con pocas probabilidades de que se les pueda controlar su PA mediante esta terapia y que por lo tanto necesitarán terapia vasodilatadora adicional. 目的 : 拉贝洛尔治疗无应答、血压(blood pressure, BP)未得到控制而需要血管扩张剂的妊娠期高血压患者, 会迅速进展为重度高血压。早期发现并进行个体化治疗可能延缓疾病。本研究中, 我们根据就诊时以及治疗开始后1 h和24 h的数据建立预测模型, 以识别对拉贝洛尔不能产生持续应答而需要血管扩张治疗的患者。 方法 : 研究人群为英国一家医院的134例高血压患者。BP>150/100 mmHg或BP>140/90 mmHg并患有系统性性疾病者口服拉贝洛尔。记录就诊时以及治疗开始后1 h和24 h的BP和血流动力学参数。采用滴定法测定拉贝洛尔剂量, 将BP维持在135/85 mmHg左右。服用最大剂量的拉贝洛尔但BP仍未得到控制的患者, 接受其他血管扩张剂治疗(硝苯吡啶)。运用二分类logistic和纵向(混合模型)数据分析, 建立能够预测高血压患者使用血管扩张剂的可能性的模型。根据就诊以及治疗后1 h和24 h的数据建立预测模型, 评估在这些时间间隔中, 与BP、心率和人口统计学变量预测效能相关的血流动力学的价值。 结果 : 队列中22%的患者产前需要其他血管扩张剂。这些患者中重度高血压以及不足月分娩低体重儿的可能性更大。治疗无应答的患者主要是黑人, 他们的BP和外周血管阻力(peripheral vascular resistance, PVR)较高, 就诊时心率和心输出量(cardiac output, CO)较低。需要血管扩张剂的患者BP和PVR开始时下降, 24 h时反弹, 而拉贝洛尔治疗应答的患者1 h和24 h时BP和PVR持续下降。两组中治疗急性期每搏输出量和CO均未下降。预测需要血管扩张治疗的最佳模型为在24h时联合种族以及纵向BP和心率的变化。该模型的检出率为100%, 假阳性率为20%, 受试者工作特征曲线下面积为0.97。 结论 : 拉贝洛尔单药治疗急性期孕妇人口统计学和血流动力学的变化, 为识别那些接受了这种治疗但BP未得到控制因而需要其他血管扩张剂的妊娠期高血压患者提供了有力工具。